Lesch-Nyhan Syndrome with Self-harming and Choreoathetosis after Improvement of Hyperuricemia: a case report - 石田, 哲朗; Murayama, Tomonori (Brazilian Journal of Case Reports, 2022)
Lesch-Nyhan syndrome (LNS) is an inborn error of metabolism. Choreoathetosis, mental retardation and self-harming are the three symptoms. A genetic test that analyses the gene encoding hypoxanthine-guanine phosphoribosyltransferase (HPRT) and blood tests showing hyperuricaemia support the diagnosis. However, the relevance of these test results to clinical symptoms is unclear. A 25 years-old man consulted our hospital for self-injury and choreoathetosis. He had epilepsy and mental retardation. He was also suffering from hyperuricemia and was prescribed allopurinol. These symptoms appeared with the improvement of hyperuricemia. He was suspected to have LNS. Metabolomic analysis of his urine before and after the allopurinol loading test was performed by gas chromatography-mass spectrometry (GC/MS) using dry filter paper urine samples as samples. The results showed that he was LNS.This case suggests that LNS is a condition that causes epileptic seizures and that rapid fluctuations in uric acid levels can cause choreoathetosis and self-harming. GC/MS using dry filter paper urine samples was a simple and valid test. This report also shows that genetic diagnosis opportunities are available to patients who have difficulty attending hospitals with advanced genetic analysis systems in urban areas.